Time-motion and technical-tactical aspects of Glory World Series matches in the male middle-heavy-weight category - Calabrese, J. C.; Silva, R. G.; Bertuzzi, R.; Lima-Silva, A. E. (International Journal of Sports Physiology and Performance, 2024)
Purpose To characterize the time structure of K1 kickboxing matches of Glory World Series (Glory) and to determine potential differences between winners and losers.